From care diamond to care pentagon : private companies and childcare provisions in Singapore. - Lee, Gabriel Heng Bin. (2011)
My Graduation Project aims to explore if, as projected by the Singapore Government, private organizations can complement the State, the market, the community and the family to help working parents support their child-caring responsibilities (Lee, 2008; Ministry of Manpower, 2008; Ministry of Community Development, Youth and Sports, 2010; Ministry of Community Development, Youth and Sports, 2011; Ministry of Manpower, 2009). As the starting point of my research, I utilize news articles and Government publications to delineate the institutional mix of care for children in the Singapore context. Thereafter, I interview key decision makers (i.e Human Resource Directors or Senior Executives) in private organizations to understand (i) how private organizations decide on what family friendly policies to implement in their respective workplaces, and for whom and (ii) the difficulties they encounter in helping their employees meet their family obligations. Major findings suggest that private organizations can be called upon to help their employees meet their child-caring obligations as they make a concerted effort to identify their employees’ family obligations, and after considering their resources, business priorities and their employees’ job responsibilities, decide on the family-friendly policies that they should implement in their respective workplaces. Finally, this study concludes by suggesting that the institutional support structures that support care provisions for children, in the Singapore context, should be re-conceptualized from a structure resembling a diamond, as suggested by Ochiai (2009: 69), to that resembling a pentagon (i.e comprising private organizations, the State, the market, the family and the community).